2010
DOI: 10.1111/j.1365-2605.2009.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical androgen‐sensitive periods of rat penis and clitoris development

Abstract: Androgen control of penis development/growth is unclear. In rats, androgen action in a foetal ‘masculinisation programming window’ (MPW; e15.5–e18.5)’ predetermines penile length and hypospadias occurrence. This has implications for humans (e.g. micropenis). Our studies aimed to establish in rats when androgen action/administration affects development/growth of the penis and if deficits in MPW androgen action were rescuable postnatally. Thus, pregnant rats were treated with flutamide during the MPW ± postnatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
109
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 36 publications
11
109
3
Order By: Relevance
“…In addition, to our knowledge, there is no report dealing with the association of micropenis and prenatal EDC contamination, whereas in experimental animals (67,68), as well as in our recent clinical experience, this is the malformation most likely to be associated with such exposure. The medical histories actually indicated that within this group of infants with an 'idiopathic' PAIS-like phenotype, 11 newborns/infants -that is, nearly 40% -had parents who reported environmental or occupational exposure to EDCs before/during the patients' fetal life and all patients presented severe forms of micropenis (16.20G5.77 mm; Fig.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, to our knowledge, there is no report dealing with the association of micropenis and prenatal EDC contamination, whereas in experimental animals (67,68), as well as in our recent clinical experience, this is the malformation most likely to be associated with such exposure. The medical histories actually indicated that within this group of infants with an 'idiopathic' PAIS-like phenotype, 11 newborns/infants -that is, nearly 40% -had parents who reported environmental or occupational exposure to EDCs before/during the patients' fetal life and all patients presented severe forms of micropenis (16.20G5.77 mm; Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Welsh et al, 2010) Human studies have also established that exposure to endocrine disrupting agents can shorten male infant perineal lengths. (Swan et al, 2005) (Torres-Sanchez et al, 2008) Thus, current studies suggest that gestational exposures may play a critical role in male fertility and adult testicular function.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that adult penis size in rats is critically dependent on androgen action during the fetal masculinization programming window, during which androgens must act to ensure correct subsequent development. Moreover, postnatal testosterone treatment does not increase the size of the adult penis beyond its 'predetermined' length, though growth toward this maximum is advanced by peripubertal testosterone treatment (29,30).…”
Section: Discussionmentioning
confidence: 98%